Comparable Levels of Inflammatory Mediators in Portal Venous Blood Collected from Organ Donors Donating after Circulatory Death and those Donating after Brain Death. (July 2018) - Reiling, Janske; Hohenhaus, Daniel M; Sweet, Matt J; Raj, Ashok S; Campbell, Catherine M; Bridle, Kim R; Santrampurwala, Nishreen; Britton, Laurence J; Crawford, Darrell HG; Dejong, Cornelis HC; Fawcett, Jonathan
Abstract : Introduction: Extended criteria donors, such as those who donate after cardiac death (DCD) are increasingly considered for transplantation. Biliary stricture formation often complicates the use of these grafts and the aetiology remains largely unknown. We have previously shown that endotoxins, in the form of lipopolysaccharides (LPS), are potent inducers of biliary injury. However, it remains unclear if endotoxaemia occurs during DCD organ donation. The aim of this study was to determine the inflammatory propensity of portal blood collected from DCD donors compared to those donating after brain death (DBD). Materials and Methods: Serial portal venous as well as hepatic venous blood samples were collected from adult DBD and DCD organ donors. An NF-κB-dependent cell-based assay was used to detect endotoxins and/or other inflammatory stimuli in the portal blood samples. β-galactosidase activity in hepatic venous samples was assessed as a marker for hepatic Kupffer cell activation. In addition, bile and bile duct tissue was collection for assessment of biliary injury. Results and Discussion: Thirty patients (nine DCD, 21 DBD) were included in this study. Compared to DBD donors, portal samples of DCD donors did not have an enhanced propensity for triggering inflammatory responses. However, Kupffer cell activation was enhanced and prolonged in DCD donors. Lactate dehydrogenase as a biomarker of biliary injury was increased in bile collected from DCD donors and histological scoring showed evidence of increased injury of peri-luminal peribiliary glands. Conclusion: In this study no evidence was found of endotoxaemia or increased propensity to produce an inflammatory response in portal blood collected from DCD donors. Despite this, hepatic Kupffer cell activation was increased and there was evidence of biliary injury. Liver Transplant Bequest, PA Research Foundation, Princess Alexandra Hospital, Brisbane, Australia. Gallipoli Medical Research Foundation, Greenslopes Private Hospital, Brisbane, Australia.